2019
DOI: 10.3390/s19020223
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensor Based Stooped Posture Estimation in Simulated Parkinson’s Disease Gaits

Abstract: Stooping is a posture which is described as an involuntary forward bending of the thoracolumbar spine. Conventionally, the stooped posture (SP) in Parkinson’s disease patients is measured in static or limited movement conditions using a radiological or optoelectronic system. In the dynamic condition with long movement distance, there was no effective method in preference to the empirical assessment from doctors. In this research, we proposed a practical method for estimating the SP with a high accuracy where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For Parkinson's disease (PD), several approaches have been developed for wearable monitoring systems during the last years, with detection of bradykinesia and tremor [97][98][99][100][101]. Machine learning has been used to detect circadian rhythms and sleep, motor, and autonomic disruption, which is suitable for objective and non-invasive monitoring of PD patients [98].…”
Section: A B Cmentioning
confidence: 99%
“…For Parkinson's disease (PD), several approaches have been developed for wearable monitoring systems during the last years, with detection of bradykinesia and tremor [97][98][99][100][101]. Machine learning has been used to detect circadian rhythms and sleep, motor, and autonomic disruption, which is suitable for objective and non-invasive monitoring of PD patients [98].…”
Section: A B Cmentioning
confidence: 99%
“…Therefore, N was chosen as 20 to eliminate the movement artifacts in each sensor axis since the sensor samples at 20 Hz. This measurement has been validated in healthy participants by comparing it with a 3D camera system with markers (Optitrack), with mean absolute errors of 0.9-1.5 • [18].…”
Section: Measurement Of Angles and Vibration Feedbackmentioning
confidence: 99%
“…Furthermore, there have been other attempts to use wearable sensors for home-based gait training in patients with PD [16,17]. Our previous study showed that measurement of the forward flexion angles of the neck and back using wearable sensors is a valid method compared with the use of a 3D camera system during simulated parkinsonian gait in healthy volunteers [18].…”
Section: Introductionmentioning
confidence: 99%
“…38 In Parkinson disease, gait pattern has been monitored via sensor built-in shoes or wearable devices. 43 Gait disturbance is an important sign of compressive myelopathy. 44,45 If gait is monitored in real time by sensors mounted on shoes or wearable devices, it is possible to promptly diagnose the progression of myelopathy in patients with cervical stenosis or ossification of posterior longitudinal ligament.…”
Section: Internet Of Things and Digital Biomarkers Associated With Spinementioning
confidence: 99%